Analisis Fungsi Perpustakaan dalam Pendidikan di Indonesia - Sri Wahyuni; Makmur Sukri (VISA: Journal of Vision and Ideas, 2023)
The function of the library is as an education center, information center and recreation center and as a medium and means of providing knowledge and insight into science. The aim is to arouse people's interest in reading, encourage the expressiveness and imagination of library users, and provide understanding to users to be able to maintain and care for collections of library materials well. Apart from that, the function of the library is also as a forum for students to increase their interest in reading with the aim of expanding their insight, whether it be religious, scientific or social knowledge, apart from student learning achievements, apart from functioning for students, libraries can also be used by teachers in schools as a place to look for reference material for teaching materials and a place to find solutions to subject matter. The aim of this research is to find out how the library functions in education. The results of the research show that there are several studies which explain that the function of the library is very important for students at the elementary, middle, high school and even at the tertiary level. This can be proven based on the results Researcher interviews with several students stated that with a library students can easily get information, get solutions related to lecture material and a place to translate foreign books.